From reading to creative writing - Abad, Heidi Emily Eusebio (The RAP Journal, 2006)
This paper shows how the task of creative writing can be merged with the more basic concerns of reading and writing. Two fun ways of structured writing are described, activities that can be collaborative and underpinned by the principle that "half the fun of reading a text is the idea that the reader is also a co-writer of its message".